Upaya Meningkatkan Aktivitas dan Hasil Belajar Matematika dengan menggunakan Model Pembelajaran Kooperatif Tipe Dua Tinggal Dua Tamu (Two Stay Two Stray) di Kelas XI TKJ 2 SMK Negeri 6 Malang - Salmah Unaizatin (Journal on Education, 2023)
The background of this research is that the mathematics learning outcomes of class XI TKJ 2 are not as expected. The things that are suspected to be causing the results of learning mathematics in class XI TKJ 2 SMK Negeri 6 Malang are that the teacher still uses the lecture/monotonous method, the facilities and infrastructure are inadequate, the activity of students in participating in the learning process is low, learning motivation and low student self-confidence. From the results of the research that the authors conducted, the following data were obtained: (1) students discussed material or lesson assignments that had been prepared by the teacher intensively in groups with an average of 66.66% (good category), (2) a pair (two people) of each group visits other groups on average reaching 83.33% (very good), (3) Two people who live in each group are in charge of sharing their work and all information with their two guests an average of 66.66% ( good category), (4) Guests excuse themselves and return to their groups on average reaching 91.66% (very good category), (5) A pair (two people) who visit again discuss giving all the information obtained from other groups on average - an average of 75% (good category) (6) All group members match and discuss their work results together an average of 66.66% (good category), (7) Individually students receive quizzes or tests from the teacher and can be done by students on average reaching 83.33% (very good), (8) The teacher gives awards to each group, based on the acquisition of individual improvement scores from basic scores to test or quiz scores reaching 83.33% (very good) . And the level of mastery of student learning on average has increased each cycle, namely cycle I reached 74%, cycle II reached 75%, and cycle III reached 77%.